Analisis Pendapatan dan Faktor-faktor Sosio-Ekonomi yang Memengaruhi Pendapatan Usahatani Padi Penerima Manfaat Embung di Desa Brani, Kecamatan Sampang , Kabupaten Cilacap - Nur, Ivan Akmal; Rifqia, Fathmi Aqinna; Rahmah, Affiatin (Universitas Galuh, 2025)
Rice is the staple crop of Indonesian society. Irrigation is very important in lowland rice farming because lowland rice plants require sufficient water for their growth. Brani Village is the only village in Sampang District, Cilacap Regency where a reservoir was built in 2021. The aim of farming is to seek maximum profits by minimizing costs. This research aims to analyze income and socio-economic factors that influence rice farming in Brani Village which benefits from the village reservoir. This research was carried out in Brani Village, Sampang District, Cilacap Regency. This research sample was taken deliberately with the criteria of farmers receiving benefits from the Brani Village reservoir. Data analysis uses income analysis, rc ratio and UOP-CDPF. The results of the analysis show that the average income per ha per planting season is IDR 23,125,096.11, the rc ratio value is 2.9 and the factors that have a real influence on profits are education, land area and insecticide prices.